ALMA opens a local window on galaxy formation - Hunt, Leslie (Il Colle di Galileo, 2014)
New observations made with ALMA, the Atacama Large Millimeter Array, an array of radio telescopes in Chile, have revealed an unexpectedly high amount of dust in a tiny, chemically unevolved galaxy in the nearby universe, SBS 0335-052. Because of the small size, high rate of star formation, and the composition of its interstellar medium, galaxies like SBS 0335-052 are thought to be similar to those that formed when the universe was very young. Such galaxies are very rare in the galactic neighborhood, but quite common in the distant universe. Our ALMA observations of SBS0335-052 thus place new and strong constraints on the way we think stars formed in early, chemically unevolved galaxies.